Debating difference group rights and liberal democracy in India - Bajpai, Rochana, 1972- (New Delhi : Oxford University Press, 2011)
This book presents a systematic account of the structure of public reasoning over group rights in India. It critiques both liberal and post-colonial narratives and constructs a framework that combines their insights for an empirical study of the norms of group rights in the country.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Minorities -- Civil rights -- India; India -- Ethnic relations